Non-Invasive Evaluation of Hepatic Fibrosis: The Diagnostic Performance of Magnetic Resonance Elastography in Patients with Viral Hepatitis B or C - Wu, Wen-Pei (PLoS One, 2015)
PURPOSE: To compare the accuracy of magnetic resonance elastography (MRE) with that of aspartate aminotransferase-to-platelet ratio index (APRI) for estimating the stage of hepatic fibrosis in patients with chronic hepatitis B virus (HBV) or chronic hepatitis C virus (HCV) infection. MATERIALS AND METHODS: We retrospectively enrolled 160 patients with chronic hepatitis and 25 healthy living liver donors. Fibrosis stage (METAVIR, F0 to F4) was determined histopathologically for all patients. APRI was recorded at the time of histopathologic examination and liver stiffness values were measured on MRE quantitative stiffness maps. The cutoff values, sensitivity, and specificity of MRE and APRI for each fibrosis stage were determined using receiver operating characteristic (ROC) analysis. RESULTS: MRE had a significantly greater area under the ROC curve than APRI score for discriminating among METAVIR stages F2-F4. Using a cutoff value of 2.80 kPa, MRE had a sensitivity of 94.4% and a specificity of 97.8% for detecting significant fibrosis (≥F2). There were no significant differences in fibrosis stage between patients with HBV and those with HCV infection. For ≥F2, the cutoffs were 2.47 kPa (100% sensitivity), 2.80 kP (maximum sum of sensitivity and specificity), and 3.70 kPa (100% specificity). CONCLUSIONS: MRE is a more accurate modality than APRI for detecting significant fibrosis in patients with chronic HBV or HCV infection. Antiviral treatment should be considered in patients with liver stiffness values ≥ 2.8 kPa.